Luwili - Yakubovich, Ilya. (Wiesbaden)
2 cilt (1. c. xv, 473 sayfa ; 2. c. 500 sayfa)
Keywords: “The Luwian language belongs to the Anatolian group of the Indo-European language family and thus constitutes a close relative of Hittite. As a rule, the Luwian cuneiform passages represent incantations embedded in Hittite religious texts. Although their full corpus was published in the twentieth century, no attempts at their cohesive philological translation has been undertaken up to now. The volume Luwili: Hittite-Luwian ritual texts attributed to Puriyanni, Kuwattalla, and Šilalluḫi (CTH 758–763) represents the first step toward achieving this goal. Ilya Yakubovich and Alice Mouton, two Hittitologists specializing in Luwian Studies and Anatolian ritualistic traditions respectively, joined efforts in order to approach the Hittite-Luwian rituals from both linguistic and anthropological perspectives. The rituals that they have edited there contain more than fifty percent of the Luwian cuneiform corpus. Their research contributes to two different fields: first, it helps the scholarly community to understand better the Luwian language, second, it impacts the study of Anatolian religions. The authors attempted to avoid the technical jargon in as much as possible, while the layout of the edition, where the transliteration and translation are aligned with each other on two symmetrical pages, should facilitate its reading“ --